PENGEMBANGAN LEMBAR KERJA SISWA (LKS) PADA MATA PELAJARAN MATEMATIKA KELAS 5 SEKOLAH DASAR (PENELITIAN PENGEMBANGAN DENGAN MATERI VOLUME KUBUS DAN BALOK DI SD IT AL-FITYAH) - Ridha Afriani Fitri; Eddy Noviana; Muhammad Fendrik (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : Based on analysis of LKS, it was found that the LKS used only contain a question without student activities and worksheets only presented in the form of a sentence without a clear picture of student understanding. This study aims to determine the feasibility of LKS in mathematics in grade 5 of primary school to the volume of cubes and beams. This type of research is the development of research. LKS developed using models ADDIE (Analysis, Design, Development, Implementation, Evaluation), but limited to the stage of development alone. The data collected is data validation and the results of the test are limited. Collecting data using validation sheet worksheets, tests and questionnaires. LKS has been designed, validated by a validator 5 in terms of both areas of the field of language, content, media and penggguna. limited trial conducted in SD IT AL-Fityah Pekanbaru. LKS validation of the results obtained an average of 94.74 with a very decent category. After LKS validated, then the test is limited to see the effectiveness of LKS developed. Data obtained from limited test is N-Gain and student response. Results N-Gain obtained a score of 0.43 if 0.3 <0.43 <0.7 categorized as normal. From the results of the questionnaire students get a good category with an average score of 85.05.Keywords : Development, LKS, ADDIE